Distinct properties of presynaptic group II and III metabotropic glutamate receptor-mediated inhibition of perforant pathway-CA1 EPSCs. - Capogna, M (2004)
I have compared the effects of group II or III metabotropic glutamate receptor (mGluR) activation on monosynaptic excitatory responses recorded intracellularly from CA1 pyramidal neurons of rat hippocampus and evoked by perforant pathway stimulation in vitro. The excitatory postsynaptic currents (EPSCs) were reduced either by the group II mGluR agonist LY354740 (500 nM, 31 +/- 6% of control) or by the group III agonist L-AP4 (400 microM, 53 +/- 5% of control). Both drugs enhanced EPSC paired-pulse facilitation (range 125-189% of control). These effects were blocked by the broad-spectrum mGluR antagonist LY341495 (1 or 20 microM) which when applied alone did not significantly change the EPSCs elicited at low (0.1-0.2 Hz) or higher (1-100 Hz) frequency of stimulation. Prior reduction of the EPSCs induced by L-AP4 did not occlude the subsequent inhibition elicited by LY354740. The effect of LY354740, but not that of L-AP4, was blocked in the presence of the cAMP analogue Sp-cAMPS (20 microM) and with the K(+) channel antagonist alpha-dendrotoxin (125 nM). In contrast, the effect of L-AP4, but not that of LY354740, was prevented by the calmodulin inhibitor ophiobolin A (25 microM) and with the N-type Ca(2+) channel antagonist omega-conotoxin-GVIA (1 microM). In the presence of the P/Q type Ca(2+) channel antagonist omega-agatoxin-IVA (400 nM), the EPSCs were depressed either by LY354740 or by L-AP4. Groups II and III mGluRs are segregated at the presynaptic terminal, and there are distinct differences between the properties of the presynaptic inhibition mediated by these two groups of receptors.